Electrophysiological study of the somatic muscle cells of ascaris suum - Thorn, Peter (The University of Edinburgh, 1989)
The electrophysiological properties of muscle cells in the nematode Ascaris suum have been studied extensively (review DeBell 1965). However, details of the ionic mechanisms regulating the spontaneous activity of the somatic muscle cell membrane are still poorly understood. The study described in this thesis, used the patch-clamp technique to examine ion channels in the soma membrane of the muscle cells. In addition, two-electrode voltage-clamp was used to observe the membrane currents of the muscle cell somata.

The patch-clamp experiments demonstrated the presence of a high-conductance chloride channel (200pS) spontaneously active at the resting potential. This channel was voltage sensitive. When the patch was depolarized the mean open time of the channel and the probability of opening were both reduced. An additional feature of this voltage sensitivity was the appearance of sub-conductance levels when the patch was depolarized.

In patches that contained more than one channel the proportion of time spent with 1,2,3...N channels open was analysed in terms of the binominal distribution. The results indicated that the binomial distribution was not a good approximation to the data. From this analysis it was concluded that either the channels in the same patch did not have the same probability of opening, or that channel openings were not independent of each other.

Experiments showed that the probability of chloride channel opening was dependent on the concentration of intracellular calcium. Increasing the concentration of calcium led to an increase in the probability of channel opening. The significance of the calcium sensitivity remains unknown. It was proposed that these channels were responsible for the high resting permeability to chloride.

The voltage-clamp experiments demonstrated the presence of two currents activated by membrane depolarization. When the muscle cells were bathed in Ringers containing calcium, depolarization activated an inward current, followed by a large outward current. The inward current increased in amplitude when the calciun concentration of the bathing solution was increased, and was blocked by lanthanizn. The outward current was activated by steps to +55 mV from a holding potential of -35 mV. This current had a steep rise and slow decay and was found to be carried by potassium ions. Depolarizing steps of increased amplitude, increased the outward current amplitude and decreased the time to peak of the current. Experiments were carried out to determine the kinetics of the outward current.

Two blockers of potassiun currents were tried in Ascaris, these were TEA and 4-AP. TEA [69 mM] was used in the study of the inward current and blocked most of the outward current. Bath application of 4-AP [5 mM] blocked a fast-transient component of the outward current. The current remaining after 4-AP application had a slow rise time, and a slow decay approximated by a single exponential, with a time constant of 1.1 s. The 4-AP resistant current shewed less steady-state inactivation than the gross outward current. Computer analysis was used to subtract the 4-AP resistant outward current from the gross outward current. The subtracted current represented the current blocked by 4-AP. The decay of the 4-AP blocked current was approximated by a single exponential, with a time constant of 10.4 ms. The function of both of these potassium conductances was thought to be to repolarize the cell after a spike.